STUDY TilE RELEASE Of NITROGEN FROM COATED UREA GRANULE: MODELLING AND EXPERIMENTAL VALIDATION - TRINH , HOAl THANH (2016)
Urea. when applied to crops is vulnerable to losses from volatilization and leaching. Controlled-release fertilizer (CRF) enhances nitrogen use efficiency by plants which not only increases the crop yields but also contributes towards environmental pollution control in terms of the alleviation of hazardous gaseous emissions and water eutrophication. This study thoroughly investigates the release of nitrogen from CRF both in modeling and experimental aspects. The experiments are conducted to provide useful information for the model and validation process. Modelling section includes several models f()f each stage of the release including lag period. constant release. and decay release stages. Firstly. this study proposes a multi diflusion model that simulates nitrogen release from coated urea particles for both the constant and decay release stages of urea.